2006
DOI: 10.1016/j.cell.2006.01.051
|View full text |Cite
|
Sign up to set email alerts
|

FSH Directly Regulates Bone Mass

Abstract: Postmenopausal osteoporosis, a global public health problem, has for decades been attributed solely to declining estrogen levels. Although FSH levels rise sharply in parallel, a direct effect of FSH on the skeleton has never been explored. We show that FSH is required for hypogonadal bone loss. Neither FSHbeta nor FSH receptor (FSHR) null mice have bone loss despite severe hypogonadism. Bone mass is increased and osteoclastic resorption is decreased in haploinsufficient FSHbeta+/- mice with normal ovarian func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
652
8
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 643 publications
(732 citation statements)
references
References 51 publications
41
652
8
14
Order By: Relevance
“…A recent study suggested that FSH might directly regulate bone mass [17], but despite the changes that occur in FSH in the patients in the present study [7], there was no correlation between either BMD or markers of bone resorption or synthesis and FSH levels. This does not rule out a role for FSH, but suggests that it alone cannot be the explanation and its apparent effects on bone may reflect that it is an indirect marker of ovarian function [18].…”
Section: Discussioncontrasting
confidence: 86%
“…A recent study suggested that FSH might directly regulate bone mass [17], but despite the changes that occur in FSH in the patients in the present study [7], there was no correlation between either BMD or markers of bone resorption or synthesis and FSH levels. This does not rule out a role for FSH, but suggests that it alone cannot be the explanation and its apparent effects on bone may reflect that it is an indirect marker of ovarian function [18].…”
Section: Discussioncontrasting
confidence: 86%
“…To better understand the biologic underpinning of how FSH acts on bone, the authors first showed that transgenic mice lacking FSHβ subunit or FSH receptor (FSHR −/− ), although severely hypogonadal, showed no evidence of bone loss (Sun et al 2006). Further evidence for the dependence of bone density on FSH levels was obtained using heterozygotic FSHβ transgenic mice (FSHβ +/− ).…”
Section: New Information On the Direct Roles Of Gonadotrophic Hormonementioning
confidence: 99%
“…Mechanistically, others and we have shown that FSH increases osteoclast formation, function, and survival through a distinct FSHR isoform [9,[26][27][28]. Wu et al [28] further showed that the osteoclastogenic response to FSH was abolished in mice lacking ITAM adapter signaling molecules.…”
Section: Introductionmentioning
confidence: 99%
“…2). As part of this paradigm shift, we later discovered that FSH directly stimulates bone resorption [9]; thus the idea that rising FSH levels during the late peri-menopause could potentially contribute to the bone loss traditionally attributed solely to low estrogen [10]. We are by no means limiting the proven importance of low estrogen in causing bone loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation